Liczebność diaspory polskiej w Obwodzie Kaliningradzkim Federacji Rosyjskiej. Zarys problematyki - Żęgota, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The issues related to Polish minority in the countries of the former Soviet Union have been intensively studied, especially since the early 1990s. It is however impossible to determine a precise number of the members of Polish minority residing in the Kaliningrad Oblast of the Russian Federation. This results from the imprecise and incomplete data presented by the local administration. The most optimistic statistics estimate Polish minority at approximately 20,000 people. On the other hand, when one refers to the ‘strict’ but certainly underestimated official data a number of nearly 5,000 is mentioned. Additionally, the issue of national affiliation is frequently related to the subjective perception of ethnic identity by the residents of the territory in question. Therefore, even though some Polish ties do exist, they do not necessarily translate directly into a mature Polish national identity, let alone the intention to admit such identity.